2020
DOI: 10.1080/21505594.2020.1809961
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 is essential for host defense against Mycobacterium abscessus infection through regulation of mitochondrial homeostasis

Abstract: The global incidence of Mycobacterium abscessus (Mabc), a rapidly growing nontuberculous mycobacterial strain that causes treatment-refractory pulmonary diseases, is increasing. Despite this, the host factors that allow for protection against infection are largely unknown. In this study, we found that sirtuin 3 (SIRT3), a mitochondrial protein deacetylase, plays a critical role in host defense against Mabc infection. Mabc decreased SIRT3 and upregulated mitochondrial oxidative stress in macrophages. SIRT3 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Thus, mtROS was measured in BMDMs by MitoSOX Red, a fluorescent probe for mtROS ( Bulua et al, 2011 ). Similar to the previous findings ( Kim Y. J. et al, 2020 ), Mabs-R infection of BMDMs led to an increase of mtROS production at 2 hpi, which was decreased with Rufomycin 4–7 treatment ( Figure 6A ). The relative fluorescent intensity level of MitoSOX was quantified to show that an increase of Rufomycin 4–7 dose gradually and significantly diminished the mtROS level of Mabs-R-infected BMDMs ( Figure 6B ).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, mtROS was measured in BMDMs by MitoSOX Red, a fluorescent probe for mtROS ( Bulua et al, 2011 ). Similar to the previous findings ( Kim Y. J. et al, 2020 ), Mabs-R infection of BMDMs led to an increase of mtROS production at 2 hpi, which was decreased with Rufomycin 4–7 treatment ( Figure 6A ). The relative fluorescent intensity level of MitoSOX was quantified to show that an increase of Rufomycin 4–7 dose gradually and significantly diminished the mtROS level of Mabs-R-infected BMDMs ( Figure 6B ).…”
Section: Resultssupporting
confidence: 90%
“…However, to evaluate its antimicrobial effects in vivo , Rufomycin 4–7 was administered to the Mabs-R-infected mice. By using the Mabs-R pulmonary infection model established in the previous work ( Kim Y. J. et al, 2020 ), it was confirmed that Rufomycin 4–7 treatment significantly decreased Mabs-R survival in the mouse lungs at 21 days post-infection (dpi) ( Figure 1A ). In addition, Rufomycin 4–7 administration significantly inhibited Mabs-R-mediated inflammatory reactions in the mouse lungs.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations